Selected soil nutrient availability, plant nutrient uptake and upland rice yield in response to rice straw and mycorrhiza application. Issue 1 (April 2021) - Syamsiyah, J; Sunarminto, B H; Hanudin, E; Widada, J; Setyawati, A; Suntoro,
Abstract: Climate change such as long drought will have an impact on food supply. Adaptation to these conditions must be conducted by improving food production. This study aims to determine the effect of straw and mycorrhizal use on soil moisture, nutrient availability and uptake as well as upland rice yield. This field trial used 3 x 2 factors, with 4 replications arranged in a Complete Randomized Block Design. The first factor consists of without straw; fresh straw (10 ton/ha); and weathered straw (10 ton/ha). The second factor was without and with mycorrhizae (5 gram/plant). The result showed that the application of fresh straw and weathered straw combine with mycorrhizal inoculation can increase soil moisture, improve the availability of soil N, P, K, increase the uptake of N, P, K. There is a positive correlation between soil moisture content with the uptake of N, P, K on the plant. Moreover, The highest grain yield (3.9 ton/ha) was obtained at the weathered straw combine with mycorrhizae. An application of rice straw in any condition can optimize soil fertility and can be used as a way of adaptation to climate change.